Endothelin-1 inhibits prolyl hydroxylase domain 2 to activate hypoxia-inducible factor-1alpha in melanoma cells. - Francesca Spinella; Laura Rosanò; Martina Del Duca; Valeriana Di Castro; Maria Rita Nicotra; Pier Giorgio Natali; Anna Bagnato (PLoS ONE, 2010)
Background The endothelin B receptor (ET(B)R) promotes tumorigenesis and melanoma progression through activation by endothelin (ET)-1, thus representing a promising therapeutic target. The stability of hypoxia-inducible factor (HIF)-1alpha is essential for melanomagenesis and progression, and is controlled by site-specific hydroxylation carried out by HIF-prolyl hydroxylase domain (PHD) and subsequent proteosomal degradation. Principal findings Here we found that in melanoma cells ET-1, ET-2, and ET-3 through ET(B)R, enhance the expression and activity of HIF-1alpha and HIF-2alpha that in turn regulate the expression of vascular endothelial growth factor (VEGF) in response to ETs or hypoxia. Under normoxic conditions, ET-1 controls HIF-alpha stability by inhibiting its degradation, as determined by impaired degradation of a reporter gene containing the HIF-1alpha oxygen-dependent degradation domain encompassing the PHD-targeted prolines. In particular, ETs through ET(B)R markedly decrease PHD2 mRNA and protein levels and promoter activity. In addition, activation of phosphatidylinositol 3-kinase (PI3K)-dependent integrin linked kinase (ILK)-AKT-mammalian target of rapamycin (mTOR) pathway is required for ET(B)R-mediated PHD2 inhibition, HIF-1alpha, HIF-2alpha, and VEGF expression. At functional level, PHD2 knockdown does not further increase ETs-induced in vitro tube formation of endothelial cells and melanoma cell invasiveness, demonstrating that these processes are regulated in a PHD2-dependent manner. In human primary and metastatic melanoma tissues as well as in cell lines, that express high levels of HIF-1alpha, ET(B)R expression is associated with low PHD2 levels. In melanoma xenografts, ET(B)R blockade by ET(B)R antagonist results in a concomitant reduction of tumor growth, angiogenesis, HIF-1alpha, and HIF-2alpha expression, and an increase in PHD2 levels. Conclusions In this study we identified the underlying mechanism by which ET-1, through the regulation of PHD2, controls HIF-1alpha stability and thereby regulates angiogenesis and melanoma cell invasion. These results further indicate that targeting ET(B)R may represent a potential therapeutic treatment of melanoma by impairing HIF-1alpha stability.